Analytical Enantio-Separation of Linagliptin in Linagliptin and Metformin HCl Dosage Forms by Applying Two-Level Factorial Design - Sushant B. Jadhav; Rahul M. Mane; Kalyanraman L. Narayanan; Popatrao N. Bhosale (MDPI AG, 2016)
A novel, stability indicating, reverse phase high-performance liquid chromatography (RP-HPLC) method was developed to determine the S-isomer of linagliptin (LGP) in linagliptin and metformin hydrochloride (MET HCl) tablets (LGP-MET HCl) by implementing design of experiment (DoE), i.e., two-level, full factorial design (23 + 3 centre points = 11 experiments) to understand the critical method parameters (CMP) and its relation with the critical method attribute (CMA), and to ensure robustness of the method. The separation of the S-isomer, LGP and MET HCl in the presence of their impurities was achieved on Chiralpak® IA-3 (Amylose tris (3, 5-dimethylphenylcarbamate), immobilized on 3 µm silica gel) stationary phase (250 × 4.6 mm, 3 µm) using isocratic elution and detector wavelength at 225 nm with a flow rate of 0.5 mL·min−1, an injection volume of 10 µL with a sample cooler (5 °C) and column oven temperature of 25 °C. Ethanol:Methanol:Monoethanolamine (EtOH:MeOH:MEA) in the ratio of 60:40:0.2 v/v/v was used as a mobile phase. The developed method was validated in accordance with international council for harmonisation (ICH) guidelines and was applied for the estimation of the S-isomer of LGP in LGP-MET HCl tablets. The same method also can be extended for the estimation of the S-isomer in LGP dosage forms.